ISOTOPIC COMPOSITION (δ13C) AND AUTHENTICITY OF COMERCIAL PULP, TROPICAL JUICES AND NECTARS OF MANGO - Figueira, Ricardo; Imaizumi, Vitor Massami; Andrade, Thalia Lee Lopes de; Venturini Filho, Waldemar Gastoni (ENERGIA NA AGRICULTURA, 2022)
ISOTOPIC COMPOSITION (δ13C) AND AUTHENTICITY OF COMERCIAL PULP, TROPICAL JUICES AND NECTARS OF MANGO RICARDO FIGUEIRA1, VITOR MASSAMI IMAIZUMI1, THALIA LEE LOPES DE ANDRADE1, WALDEMAR GASTONI VENTURINI FILHO1 1Departamento de Produção Vegetal/Área Horticultura, Faculdade de Ciências Agronômicas, UNESP. Av. Universitária, 3780 - Altos do Paraíso, CEP 18610-034, Botucatu, SP, Brasil. ricardo.figueira@unesp.br; vtr_massami@hotmail.com; thalialda@hotmail.com; waldemar.venturini@unesp.br ABSTRACT: The aim of this study was to quantify the carbon-13 of C3 photosynthetic cycle in commercial pulps, tropical juices and nectars of mango through the technique of stable isotopes of carbon to identify the beverages at odds with Brazilian law. The relative isotope enrichment of cane sugar, additives, laboratory-fabricated beverages and commercial beverages was measured in Isotopic Ratios Mass Spectrometer (IRMS). To estimate the error of the isotopic methodology sweetened tropical juices and nectars were produced in laboratory according to their Identity and Quality Standard (IQS) and also adulterated beverages with amount of pulp below of the established by Brazilian law. In these beverages, the theoretical percentage of C3 source was calculated and the practical percentage was determined in IRMS. The difference between these measurements represented the error of the method. Twenty-two brands of non-alcoholic mango beverages were analyzed. According to the minimum soluble solids contents established by Brazilian legislation, two brands were classified as adulterated. However, isotopic analysis of carbon indicated that 12 commercial beverages were adulterated. Even in a small number of analyzed samples, adulterated beverages (54.55 %) were found. This fact demonstrates the need for greater control in this agribusiness sector. Keywords: Mangifera indica, legislation, quality, adulteration, carbon-13 COMPOSIÇÃO ISOTÓPICA (δ13C) E AUTENTICIDADE DE POLPAS, SUCOS TROPICAIS E NÉCTARES COMERCIAIS DE MANGA RESUMO: O objetivo deste trabalho foi quantificar o carbono do ciclo fotossintético C3 em polpas, sucos tropicais e néctares de manga comerciais por meio da técnica dos isótopos estáveis do carbono para identificar as bebidas em desacordo com a legislação brasileira. O enriquecimento isotópico relativo dos açúcares de cana, aditivos, bebidas fabricadas em laboratório e bebidas comerciais foi mensurado no Espectrômetro de Massa de Razões Isotópicas (IRMS). Para estimar o erro do método isotópico foram produzidos em laboratório sucos tropicais adoçados e néctares conforme a legislação brasileira e também bebidas adulteradas (com quantidade insuficiente de polpa). Nestas bebidas foi calculada a porcentagem teórica de fonte3. A porcentagem prática foi determinada no IRMS. A diferença entre essas quantificações representou o erro do método. Para determinar a legalidade das bebidas comerciais foi calculado o Limite de Legalidade tendo como referência o PIQ de cada bebida. Vinte e duas marcas de bebidas não alcoólicas de manga foram analisadas. De acordo com o teor de sólidos solúveis estabelecido pela legislação, duas marcas foram classificadas como adulteradas. Porém, a análise isotópica do carbono quantificou a adulteração em doze marcas. Mesmo com um pequeno número de amostras analisadas, 54,55 % estavam adulteradas. Esse fato demonstra a necessidade de maior controle nesse setor do agronegócio. Palavras-chave: Mangifera indica, legislação, qualidade, adulteração, carbono-13.